The Contribution of Integrative Physics Textbooks in Higher Education and Their Impact on Islamic Education Goals - Cahyadi, Dadi; Handrianto, Budi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the dominance of the modern scientific perspective in university science education, which often separates natural sciences from faith-based values. To bridge this gap, developing Physics textbooks that integrate a faith-based approach is crucial. The research explores how Physics textbooks can contribute to achieving Islamic educational goals in universities, employing a qualitative method including literature reviews and textbook analysis. The findings reveal that integrative Physics textbooks can significantly contribute to linking Physics concepts with Islamic values, creating a holistic learning approach. This study proposes a concept for integrative Physics teaching materials, incorporating the history of science and the philosophy of science, preparing students to master Physics and develop strong faith.